Development of learning devices based on discovery learning model on global warming topic to improve student learning motivation and outcome - Mega Safana; Muhammad Zuhdi; Jannatin Ã¢â¬ËArdhuha (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study aims to develop learning devices based on a discovery learning model on global warming topics that are feasible to improve student physics learning motivation and outcome. The research is a research and development study with the ADDIE model standing for Analyze, Design, Development, Implement, and Evaluate. The developed research instruments are syllabus, Lesson Plan (LP), Student Worksheet (SW), learning video, and test instrument. Meanwhile, data collection instruments include a validation sheet, motivation questionnaire, along pre-test and post-test sheets. Paired sample T-test was used to assess the comparative hypothesis of the two samples' average. The research instruments were developed at the Department of Physics Education Laboratory, Faculty of Teacher Training and Education, University of Mataram and applied in XI MIA 1 class of State Madrasah Aliyah 1 Mataram. Those instruments were syllabus, LP, SW, and test instruments. The developed learning devices based on the discovery learning model were assessed by three expert validators, physics lecturers, resulting in learning devices with